(untitled) (World Bulletin of Social Sciences, 2026)
This article examines the lexical-semantic structure of the concept “teen/adolescence” in the English language. It identifies core lexical units that directly denote adolescents, such as teen, teenager, adolescent, and youth, as well as peripheral words that describe their psychological, social, and behavioral characteristics. Peripheral lexical units include terms related to emotions, identity, independence, social relationships, education, daily activities, and behavioral traits. The study demonstrates that the concept of adolescence is multidimensional, reflecting not only age but also emotional development, social roles, and cultural context. Understanding this lexicalsemantic structure provides insight into how language represents adolescence in contemporary society.